Bedload sediment transport model for revealing the multi-year trend of polychlorinated biphenyl contamination in the river sediment (Kupa, Croatia) - Herceg Romanić, Snježana; Jaćimović, Nenad; Mendaš, Gordana; Fingler, Sanja; Stipičević, Sanja; Jakšić, Goran; Popović, Aleksandar; Jovanović, Gordana (Environmental geochemistry and health, 2023)
This article investigated the multi-year polychlorinated biphenyl (PCB) burden of the sediment collected along the Kupa River flow in Croatia using the bedload sediment transport model. Kupa, as the natural border between Croatia and Slovenia, belongs to the water system Krupa (Slovenia) → Lahinja (Slovenia) → Kupa (Croatia) → Sava → Danube → Black Sea. From 1962 to 1985, the total quantity of waste calculated for pure PCBs, released by a capacitor manufacturer into the environment within various locations of the Krupa River in Slovenia, was 70 tons. Krupa River (Slovenia) has become one of the most PCB-polluted rivers in Europe, and consequently, PCBs have been detected in the Kupa River (Croatia). Model application revealed that contamination of the Kupa River (Croatia) started significantly earlier than 1983, when a high concentration of PCB was detected for the first time in the Krupa River (Slovenia), with probably significantly higher sediment concentrations at the upstream boundary of the Kupa. A slow concentration changes and PCB accumulation in the sediment should be expected downstream compared to the upstream boundary, governed mainly by high flow events. The PCBs in sediments from 2020/2021 are markedly different after the Lahinja confluence with Kupa (0.2–0.6 μg kg −1 vs. 1.4–34.3 μg kg −1 ). Measurements of PCBs in Kupa sediment suggest that the intake of PCB has not yet been completely stopped, which should be confirmed by detailed monitoring in the future. The contamination situation observed in the Kupa River represents an excellent example of the persistency of PCBs in the environment.